Iron deposition is associated with differential macrophage infiltration and therapeutic response to iron chelation in prostate cancer - Leftin, Avigdor (Sci Rep, 2017)
Immune cells such as macrophages are drivers and biomarkers of most cancers. Scoring macrophage infiltration in tumor tissue provides a prognostic assessment that is correlated with disease outcome and therapeutic response, but generally requires invasive biopsy. Routine detection of hemosiderin iron aggregates in macrophages in other settings histologically and in vivo by MRI suggests that similar assessments in cancer can bridge a gap in our ability to assess tumor macrophage infiltration. Quantitative histological and in vivo MRI assessments of non-heme cellular iron revealed that preclinical prostate tumor models could be differentiated according to hemosiderin iron accumulation—both in tumors and systemically. Monitoring cellular iron levels during “off-label” administration of the FDA-approved iron chelator deferiprone evidenced significant reductions in tumor size without extensive perturbation to these iron deposits. Spatial profiling of the iron-laden infiltrates further demonstrated that higher numbers of infiltrating macrophage iron deposits was associated with lower anti-tumor chelation therapy response. Imaging macrophages according to their innate iron status provides a new phenotypic window into the immune tumor landscape and reveals a prognostic biomarker associated with macrophage infiltration and therapeutic outcome.